THE NATURE OF THE WESTERN TYPE OF AMERICAN ENGLISH (GA) AND THE SOUTHERN TYPE OF AMERICAN ENGLISH - Isakova Zarinabonu Alisher qizi (TADQIQOTLAR, 2025)
ABSTRACT This  paper  analyzes  two  principal  varieties  of  American  English:  General American (GA), representing the western type, and Southern American English. The discussion  centers  on  the  phonetic  characteristics  that  differentiate  these  dialects, specifically  vowel  systems,  consonant  realization,  and  prosodic  features. Comprehending  these  variations  is  vital  for  phonetic  research  and  for  practical applications in language instruction.